Dynamics of stainless steel corrosion based on the theory of phase space reconstruction and chaos. Issue 3 (3rd May 2016) - Men, Hong; Sun, Bin; Zhao, Xiao; Li, Xiujie; Liu, Jingjing; Xu, Zhiming
Abstract : Purpose: The purpose of this study is to analyze the corrosion behavior of 304SS in three kinds of solution, 3.5 per cent NaCl, 5 per cent H2 SO4 and 1 M (1 mol/L) NaOH, using electrochemical noise. Design/methodology/approach: Corrosion types and rates were characterized by spectrum and time-domain analysis. EN signals were evaluated using a novel method of phase space reconstruction and chaos theory. To evaluate the chaotic characteristics of corrosion systems, the delay time was obtained by the mutual information method and the embedding dimension was obtained by the average false neighbors method. Findings: The varying degrees of chaos in the corrosion systems were indicated by positive largest Lyapunov exponents of the electrochemical potential noise. Originality/value: The change of correlation dimension in three kinds of solution demonstrated significant differences, clearly differentiating various types of corrosion.